THE REALITY OF MEDICAL SOLID WASTE COLLECTION, TRANSPORTATION, STORAGE AND DISPOSAL AT THU DUC DISTRICT HOSPITAL, HO CHI MINH CITY IN 2019 (Vietnam Journal of Community Medicine, 2021)
There are 11 rooms and 38 departments with 1791 staffs in Thu Duc District Hospital. Moreover, there are above 6000 patients coming for examination and approximately over 900 in-patients at the hospital. Although the medical solid waste management was concentrated and focused on, there is still some insufficient points that need to be researched. Therefore, we are now proceeding in researchingour aim to describe the reality of medical solid waste management at Thu Duc District Hospital in 2019 and evaluate the factor that affects the waste management. The method for this research is cross-section descriptive research. We have observed all tools, equipments used for managing medical solid waste, and observed the medical solid waste classification in 36 departments/ clinical units, paraclinical, also have used designed inventory. The ratio of the department that meet thegoals in general of collecting, transporting, storage and waste disposal is not really high, only 75%, in which that the ratio for collecting by department only is lowest with 77.8%; next for collecting the waste by equipments with 80.6%; for waste classification by equipments is 83.3%.
Keywords: Medical solid waste, medical solid waste management, dangerous uninfected medical solid waste